Fabrication and Microwave Absorption Properties of Fe0.64Ni0.36-NiFe2O4 Nanocomposite - Yan, Xu; Xue, Desheng (Nano-Micro Letters, 2012)
Fe0.64Ni0.36−NiFe2O4 nanocomposite was performed with partially reducing NiFe2O4 nanoparticles in Ar/H2 ambient. The microwave and static magnetic properties were investigated. The results showed that the nanocomposite was characterized with enhanced microwave absorption properties. The optimal reflection loss (RL) of the nanocomposite reached −24.8 dB at 14 GHz for an absorber thickness of 1.5 mm. Meanwhile, a broad bandwidth for RL<-10 dB was obtained in the range of 3.1–15.1 GHz for an absorber thickness from 1.0 to 4.0 mm. The enhancement is attributed to the increase of dielectric and magnetic loss after reducing procedure.